Etyczne aspekty kredytu - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2010)
A financial crisis of 2008 showed a global meaning of ethical dimension of the credit institution because lack of financial subjects’ responsibility is regarded as one of the causes of the world breakdown. The author attempts to reconstruct the role of credit in the society and economy, especially an evolution of its ethical aspects is analysed. It is aimed to catch and understand the phenomenon of responsibility for the effects of this institution activity which proved dramatic more and more often both for individuals and for the whole society.